2000
DOI: 10.1139/l00-069
|View full text |Cite
|
Sign up to set email alerts
|

Road contact stresses and forces under tires with low inflation pressure

Abstract: Many field trials have been undertaken to demonstrate the benefits of reducing the inflation pressure of the tires of heavily loaded haul vehicles, but few carefully controlled laboratory studies have been performed. An earlier full scale laboratory study indicated that tire inflation pressure had far less effect on subgrade strains for unpaved, single-layer granular road structures than the tire loading itself, so attention was directed to the behaviour of the granular base at the tire tread -road surface int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(1 citation statement)
references
References 7 publications
(17 reference statements)
0
0
0
Order By: Relevance
“…They found that vehicle speed had almost no effect on the vertical contact stress but had a significant influence on the longitudinal contact stress; the longitudinal stress on the pavement and the tire changed direction twice from the stationary state to the rolling state. Douglas et al [48] tested the distribution of vertical and longitudinal pressures between the tire and the pavement under different tire pressures and loads. Their test was a full-scale laboratory test and confirmed Tielking's analysis of the contact stresses.…”
Section: Mechanical Characteristicsmentioning
confidence: 99%
“…They found that vehicle speed had almost no effect on the vertical contact stress but had a significant influence on the longitudinal contact stress; the longitudinal stress on the pavement and the tire changed direction twice from the stationary state to the rolling state. Douglas et al [48] tested the distribution of vertical and longitudinal pressures between the tire and the pavement under different tire pressures and loads. Their test was a full-scale laboratory test and confirmed Tielking's analysis of the contact stresses.…”
Section: Mechanical Characteristicsmentioning
confidence: 99%